Expert Novice Dialog (END) Di Masa Pandemi Covid-19 Untuk Menilai Kemampuan Komunikasi Sains: (Expert Novice Dialogue (END) During The Covid-19 Pandemic To Assess Science Communication Ability) - Evi Paojiah; Suhendar Suhendar; Gina Nuranti (BIODIK, 2021)
This study aims to determine the science communication skills of high school students are assessed using the Expert-Novice Dialog (END) method with the help of Google Suite. This research was conducted at one of the Sukabumi City Senior High Schools in April the second week of 2021. This study uses a descriptive method with a quantitative approach. The sampling technique used in this research is purposive sampling technique. The subjects used in this study were students of class X SMA, totaling 60 students consisting of 20 Experts and 40 Novices. Data collection were carried out digitally with the help of Google Suite. The concept of the selected material is a change in environmental balance. The instruments used in this research are science communication skills rubric, observation rubric, novice concept test and student response questionnaires. The results showed that the science communication skills of students in one of the Sukabumi City Senior High Schools were assessed using the Expert-Novice Dialog (END) method assisted by Google Suite an average of 67% which was included in the "Enough" category. Mastery of the novice concept is categorized as "Good" with an average score of 80.25%. Through the response questionnaire, it is known that the END method generally helps students in practicing science communication skills and understanding concepts. abstrak. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Teknik pengambilan sampel yang digunakan pada penelitian ini adalah teknik purposive sampling. Subjek yang digunakan pada penelitian ini adalah peserta didik kelas X SMA yang berjumlah 60 peserta didik terdiri dari 20 Expert dan 40 Novice. Teknik pengambilan data dilakukan secara digital berbantuan google suite.Konsep materi yang dipilih adalah perubahan keseimbangan lingkungan. Instrumen yang digunakan dalam penelitian ini adalah rubrik kemampuan komunikasi sains, rubrik observasi, test konsep novice dan angket respon peserta didik Hasil penelitian menunjukan bahwa kemampuan komunikasi sains pesera didik di salahsatu SMA Negeri Kota Sukabumi yang dinilai dengan metode Expert-Novice Dialog (END) berbantuan google suite rata-rata sebesar 67% termasuk dalam kategori â€œcukupâ€. Penguasaan konsep novice dikategorikan â€œBaikâ€ dengan nilai rata-rata 80,25%. Melalui angket respon diketahui bahwa Metode END pada umumnya membantu peserta didik dalam melatih kemampuan komunikasi sains dan memahami konsep. Kata Kunci : Penilaian, Kemampuan komunikasi sains, Metode Expert-Novice Dialog (END), Google Suite